A COMPARATIVE STUDY OF THE THREE B.ED. CURRICULA: EMPHASIZING ON THE TEACHER EDUCATION IN POST-INDEPENDENCE ERA - Mandal, Rini; Mete, Jayanta (International Journal of Research -GRANTHAALAYAH, 2023)
Introduction: Teacher education or teacher training denotes the formal programs, actions, guidelines, and requirements, planned to prepare teachers by inculcating information, beliefs, manners, methodologies, and abilities in a way that is needed by them for performing their responsibilities proficiently in the classroom, institution and in a larger area. Objectives: To understand and find out the differences between the three B.Ed. curricula. Methodology: The study is based on Documentary Analysis. For data collection, the syllabus of B.Ed. 1-year, 2-year & 4-year Integrated B. A. B. Ed. and B.Sc. B. Ed. Courses have been followed here. Besides journals, articles, educational policies, and recommendations of various commissions regarding the preparation of teachers are reviewed. Findings: In the 4-Year Integrated B. A. B. Ed. and B. Sc. B. Ed. programme student-teachers have to prepare two school subjects, the duration of the school internship will be of 20 weeks, 120 Lesson plans need to be prepared, Final teaching will be assessed only by internal evaluators, too much importance is given to the subject of Education, which can hamper mastery of other subjects. Conclusion: The model will certainly provide the necessary professional touch to the skills of teachers in the upcoming time and will benefit the students by providing them with the opportunity to acquire a dual degree and mastery of multiple skills if the policy is implemented properly.